The impacts of rising vapour pressure deficit in natural and managed ecosystems - Novick, Kimberly A.; Ficklin, Darren L.; Grossiord, Charlotte; Konings, Alexandra G.; Martínez‐Vilalta, Jordi; Sadok, Walid; Trugman, Anna T.; Williams, A. Park; Wright, Alexandra J.; Abatzoglou, John T.; Dannenberg, Matthew P.; Gentine, Pierre; et al. (Plant, cell and environment, 2024)
An exponential rise in the atmospheric vapour pressure deficit (VPD) is among the most consequential impacts of climate change in terrestrial ecosystems. Rising VPD has negative and cascading effects on nearly all aspects of plant function including photosynthesis, water status, growth and survival. These responses are exacerbated by land–atmosphere interactions that couple VPD to soil water and govern the evolution of drought, affecting a range of ecosystem services including carbon uptake, biodiversity, the provisioning of water resources and crop yields. However, despite the global nature of this phenomenon, research on how to incorporate these impacts into resilient management regimes is largely in its infancy, due in part to the entanglement of VPD trends with those of other co‐evolving climate drivers. Here, we review the mechanistic bases of VPD impacts at a range of spatial scales, paying particular attention to the independent and interactive influence of VPD in the context of other environmental changes. We then evaluate the consequences of these impacts within key management contexts, including water resources, croplands, wildfire risk mitigation and management of natural grasslands and forests. We conclude with recommendations describing how management regimes could be altered to mitigate the otherwise highly deleterious consequences of rising VPD. Summary statement Rising atmospheric vapour pressure deficit (or VPD) is one of the most widespread and significant consequences of climate warming for terrestrial ecosystems. This article reviews the mechanistic bases of these usually deleterious impacts and synthesises that information into a set of management recommendations to mitigate them.